2016
DOI: 10.1080/21622965.2015.1129608
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological presentation and adaptive skills in high-functioning adolescents with visual impairment: A preliminary investigation

Abstract: Studies in infants and young children with congenital visual impairment (VI) have indicated early developmental vulnerabilities, conversely research with older children and adults have highlighted areas of cognitive strength. A minimal amount is known, however, about the possible combination of strengths and weaknesses in adolescence, and this present study therefore aims to explore the neuropsychological presentation and adaptive behavior profile in high-functioning adolescents with congenital VI. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…The results of the current study indicated reduced adaptive behaviour in children with visual impairment across domains of practical, social, and conceptual function. These results mirror previous studies that also reported reduced adaptive behaviour in school-age children and in adolescents with congenital VI (Greenaway, Pring, Schepers, Isaacs, & Dale, 2017;Metsiou et al, 2011;Papadopoulos, Metsiou, & Agaliotis, 2011a). In line with these reports, the most pronounced difficulties were found for children with S/PVI in practical aspects of adaptive behaviour, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study indicated reduced adaptive behaviour in children with visual impairment across domains of practical, social, and conceptual function. These results mirror previous studies that also reported reduced adaptive behaviour in school-age children and in adolescents with congenital VI (Greenaway, Pring, Schepers, Isaacs, & Dale, 2017;Metsiou et al, 2011;Papadopoulos, Metsiou, & Agaliotis, 2011a). In line with these reports, the most pronounced difficulties were found for children with S/PVI in practical aspects of adaptive behaviour, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Ratings of strengths and difficulties (SDQ) further indicated that peer relationships are an area of concern for children with VI. Difficulties in social function have been consistently observed across pre-school, middle childhood, and adolescents in congenital VI (Bathelt et al, 2017;Greenaway et al, 2017;Jure et al, 2016;Tadić et al, 2010). Reported difficulties were most pronounced for children with S/PVI, but ratings in the MVI group overlapped with both the S/PVI and control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verbal comprehension was assessed using verbal subtests of the Wechsler Intelligence Scale for Children 4th edition (WISC-IV) (Wechsler, 2004). Verbal subtests of previous and current editions of the WISC have also been used with children with VI (Greenaway et al, 2016; Dekker, 1993; Tillman, 1973; Tillman and Bashaw, 1968; Witkin et al, 1968). The administered subtests included all items of the Verbal Comprehension composite score (Vocabulary, Similarities, Comprehension).…”
Section: Methodsmentioning
confidence: 99%
“…This means that the choice of clothing is determined by commercial availability, but parents/caregivers ultimately prescribe item purchase. As parents play a crucial role in initiating and supporting the development and acquisition of independence skills, parental influence resulting from culture, expectations, and willingness can affect skill development (Taverna et al, 2011;Greenaway et al, 2017;Ayllón et al, 2019).…”
Section: Introductionmentioning
confidence: 99%